Multi-criteria supplier evaluation/selection by considering ethical factors under uncertainty. (9th August 2019) - Azadfallah, Mohammad
In recent years, companies pay more attention to ethic and ethical issues have become a key determinant of performance in the business arena. This is not an area which has been systematically examined. From the literature, it appears to be assumed that the supplier selection is multiple attribute decision making/multiple criteria decision making (MADM/MCDM) problem, information and performances usually incomplete and uncertain, and supplier ethics is becoming another key factor to consider, too. The question typically posed is; how ethical factor can be modelled formally for an established MCDM models? In this paper, we propose a new interval TOPSIS-based procedure to resolve this problem. So, the proposed method has a capability to identify a measure of unethical performance with input and output system balancing, and consist of the two-step. In the first step, a new interval TOPSIS-based approach is used, results of this step are input for conventional interval TOPSIS method in the second step. The results indicate that the accuracy of the decision has been increased by considering the ethical factors.